Azadirachtin-based biopesticide affects the respiration and digestion in Anticarsia gemmatalis caterpillars. (3rd April 2022) - Farder-Gomes, Cliver Fernandes; Saravanan, Meenakshi; Martínez, Luis Carlos; Plata-Rueda, Angelica; Zanuncio, José Cola; Serrão, José Eduardo
Abstract: Anticarsia gemmatalis (Lepidoptera) is a soybean pest controlled mainly with synthetic insecticides. The effects of azadirachtin-based biopesticide (Azamax ® ) were investigated against A. gemmatalis caterpillars for toxicity, survival, respiration, antifeeding effects, and midgut histopathology. Concentration–mortality show LC50 = 0.58 g L −1 to A. gemmatalis . Survival caterpillars decrease to 30% after biopesticide exposure. The biopesticide decrease the respiration rate and food consumption by caterpillars. The midgut of insects exposed to the biopesticide undergoes histopathological changes. Azadirachtin-based biopesticide exhibits lethal and sublethal on A. gemmatalis and can be used in integrated pest management programs as an alternative to control this pest.